Validation of a dual-task exercise program to improve balance and gait speed in older people (DualPro): a Delphi study - Luz Adriana Varela-Vásquez; Montserrat Girabent-Farrés; Almudena Medina-Rincón; Sandra Rierola-Fochs; Javier Jerez-Roig; Eduard Minobes-Molina (PeerJ, 2022)
Background Most physical exercise programs for older people work the physical component in isolation, excluding cognitive aspects. Previous studies reported that both components (physical and cognitive) are necessary for correct functioning of older people in the society. Purpose To create and validate a dual-task exercise program (DualPro) to improve balance and gait speed in older people. Methods Expert consensus or the Delphi Method was used for validation. A group of 17 experts in neurorehabilitation and geriatrics was recruited to assess the proposed exercise program. They were selected taking into account their experience in clinical practice as well as their knowledge of the subject through the use of the expert competence coefficient (K). Online questionnaires were sent with a total of 11 exercises, which had to be rated using a “Likert” scale from 1 to 7. Results Two rounds were conducted to achieve 100% consensus in all exercises. The interquartile range of each exercise in both rounds was stable. During the second round, the relative interquartile range was less than 15% in all the questions, thus demonstrating consensus among the experts. Conclusion Experts in neurorehabilitation and geriatrics have concluded the validity of the progressive and systematized program of dual-task exercises focused on improving balance and gait speed for older people. This exercise program can help in the homogenization of the use of dual-task exercises in future studies and in professional practice.